Jørgen Elbek: Litteraturen i dag. - Michelsen, William (Grundtvig-Studier, 1970)
Reviews of literature on Grundtvig Jørgen Elbek, Literaturen i dag. Artikler om ældre o g nyere forfattere Rev. by William Michelsen This book contains, among other things, reprints of three essential studies on Grundtvig, it is prefaced by an excellent defence of existential criticism, and it concludes in considerations of literature and its application in education, inspired, in part, by Grundtvig’s view of poetry. Therefore the review calls attention to Elbek’s interpretations of “Nyaars-Morgen” and “Sang-Værk” as valuable contributions towards the intrepretation of Grundtvig’s poetry in general. In volume his Grundtvig studies do not yet equal Toldberg’s and Uffe Hansen’s, but in quality he is equal to Magnus Stevns. And over these scholars he has the advantage of being familiar with literature at large, which makes his assessment of Grundtvig a weighty one. A full appreciation of Elbek’s interpretations presupposes that the poems are fresh in one’s memory, and thus the book is a strong incentive to re-reading Grundtvig’s poetry.